2012
DOI: 10.1002/dneu.22009
|View full text |Cite
|
Sign up to set email alerts
|

Running throughout middle‐age improves memory function, hippocampal neurogenesis, and BDNF levels in female C57BL/6J mice

Abstract: Age-related memory loss is considered to commence at middle-age and coincides with reduced adult hippocampal neurogenesis and neurotrophin levels. Consistent physical activity at midlife may preserve brain-derived neurotrophic factor (BDNF) levels, new cell genesis and learning. In the present study, 9-month-old female C57Bl/6J mice were housed with or without a running wheel and injected with bromodeoxyuridine (BrdU) to label newborn cells. Morris water maze learning, open field activity and rotarod behavior … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
208
0
8

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 269 publications
(237 citation statements)
references
References 55 publications
18
208
0
8
Order By: Relevance
“…Intravenous BDNF delivery enhances post-stroke sensorimotor recovery and stimulates neurogenesis [62]. It has also been demonstrated that BDNF up-regulation following exercise is associated with a robust activation of survival pathways that enhance adult neurogenesis in experimental animals [63,64]. Currently, it is unknown whether WBV leads to increases in hippocampal BDNF and whether this response promotes neurogenesis associated with improved cognitive outcome after stroke, but we suspect that this may be the missing link between WBV and exercise.…”
Section: Discussionmentioning
confidence: 99%
“…Intravenous BDNF delivery enhances post-stroke sensorimotor recovery and stimulates neurogenesis [62]. It has also been demonstrated that BDNF up-regulation following exercise is associated with a robust activation of survival pathways that enhance adult neurogenesis in experimental animals [63,64]. Currently, it is unknown whether WBV leads to increases in hippocampal BDNF and whether this response promotes neurogenesis associated with improved cognitive outcome after stroke, but we suspect that this may be the missing link between WBV and exercise.…”
Section: Discussionmentioning
confidence: 99%
“…As expected, this increase in neurogenesis in old exercised animals was associated with an improvement in their abilities in acquiring reference memory in the working memory (WM) compared with sedentary ones (van Praag et al 2005). In addition, exercise starting at the onset and continued throughout middle age also improves spatial memory and enhances neurogenesis (Marlatt et al 2012). Further, exposure of rats to an enriched environment during the prenatal period, the early postnatal period (Koo et al 2003), and adulthood (Nilsson et al 1999) also increased both neurogenesis and spatial learning abilities in the water maze.…”
Section: Correlationsmentioning
confidence: 93%
“…While there is still much focus on the signalling mechanisms by which exercise effects are mediated, upregulation of the neurotrophin brain-derived neurotrophic factor (BDNF) has been consistently reported following exercise interventions. Increased expression of hippocampal BDNF and its receptor TrkB has been observed following voluntary wheel running (Gibbons et al, 2014;Kobilo et al, 2011;Marlatt et al, 2012) and forced treadmill exercise Griffin et al, 2009;Wu et al, 1985). At a behavioural level, improvements in spatial learning and memory, associative learning and recognition memory have all been observed in animals following exercise training.…”
Section: Adult Hippocampal Neurogenesis and Exercisementioning
confidence: 99%